2016
DOI: 10.1016/j.jcin.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Vasomotor Function Comparative Assessment at 1 and 2 Years Following Implantation of the Absorb Everolimus-Eluting Bioresorbable Vascular Scaffold and the Xience V Everolimus-Eluting Metallic Stent in Porcine Coronary Arteries

Abstract: Absorb BVS-implanted coronary arteries demonstrate early functional restoration of the scaffolded and adjacent segments at 1 year, which is preserved up to 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…Introduction of the Absorb BRS was a milestone in treatment of obstructive coronary artery disease. The positive initial safety reports,9 the restoration of the vasomotor function,10 the late lumen enlargement11 and the full resorption documented after 5 years12 were encouraging for the technology. However, recent reports on early luminal scaffold dismantling,4 increased rates of scaffold thrombosis1 2 and a late increase in target lesion failures in comparison with permanent DES2 3 indicates that limitations of first generation BRS affect outcomes negatively.…”
Section: Discussionmentioning
confidence: 84%
“…Introduction of the Absorb BRS was a milestone in treatment of obstructive coronary artery disease. The positive initial safety reports,9 the restoration of the vasomotor function,10 the late lumen enlargement11 and the full resorption documented after 5 years12 were encouraging for the technology. However, recent reports on early luminal scaffold dismantling,4 increased rates of scaffold thrombosis1 2 and a late increase in target lesion failures in comparison with permanent DES2 3 indicates that limitations of first generation BRS affect outcomes negatively.…”
Section: Discussionmentioning
confidence: 84%
“…The vasomotion of the scaffolded/stented vessels between the BVS and Xience DES ( Figure 4A,B) was examined in a preclinical porcine model. The results showed that vessels with the BVS demonstrated significantly restored in-scaffold vasomotor function at 1 and 2 years followup (34). Similarly, Elixir's DESolve BRS reported an increase in the scaffold area between 3 and 6 months.…”
Section: Vasomotion After Brs Implantationmentioning
confidence: 79%
“…Plain-balloon injury, bare-metal stents (BMS) and drug-eluting stents (DES) all result in acute endothelial and VSMC dysfunction [25,61]. In addition to the directly stented section, proximal and distal segments may experience impaired vascular responses [62][63][64].…”
Section: Functional Changesmentioning
confidence: 99%